2020
DOI: 10.1111/jan.14344
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of hope in cancer patients during treatment: A systematic literature review

Abstract: AimTo identify the associated factors of hope during treatment in cancer patients.BackgroundHope is very important to cancer patients at all stages of the disease process. Hope is seen as an important coping mechanism. Most research about hope in cancer patients considered the end of life or in palliative care. Several and different factors are associated with hope. It is not yet sufficiently clear which factors are associated with hope during the treatment.DesignA systematic literature review of quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 66 publications
2
29
3
3
Order By: Relevance
“…Results showed that the mean score of hope had a significant relationship with educational level so that participants with university degrees had greater hope compared with illiterate participants. Two former studies also reported the same finding (22,33). This may be attributed to more access of highly educated people to information resources such as internet, books, magazines, and articles which can enhance a person's hope.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Results showed that the mean score of hope had a significant relationship with educational level so that participants with university degrees had greater hope compared with illiterate participants. Two former studies also reported the same finding (22,33). This may be attributed to more access of highly educated people to information resources such as internet, books, magazines, and articles which can enhance a person's hope.…”
Section: Discussionsupporting
confidence: 64%
“…For example, some studies showed that patients' greater knowledge about cancer, its treatments, and its prognosis did no negatively affect their hope (20,21). Other studies revealed that knowledge and awareness about cancer can be associated with positive consequences (15,22). Contrarily, some studies showed that acquiring knowledge about cancer and its different aspects was associated with a stronger emotional reaction to the illness and hopelessness (13,23).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients suffer from limitations in prognosis and treatment. These limitations can often lead to the disappearance of the joy of life (3). In this study, there was no significant difference between mean fatigue scores and mean score of gender, age, marital, educational and employment status of the patients.…”
Section: Discussioncontrasting
confidence: 54%
“…According to the World Cancer Report 2020, there were 19.3 million new cases and 10 million cancer-related deaths worldwide in 2020 (1). Cancer, a major health problem of modern medicine and human, is perceived as a serious and chronic illness, which causes fear, hopelessness, guilt, helplessness, unbearable pain, fatigue, abandonment, death and evokes the feeling and ideas of death, creates anxiety and chaos in patients and their families (2)(3)(4). Fatigue is the most common symptom in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that nurses should pay attention to improve patients' positive attitudes towards breast cancer and alleviate the negative thoughts during chemotherapy through psychological counselling. A systematic review showed that the hope measured by HHI is related to age, education level, marital status and religious support and has nothing to do with the type of cancer, treatment and cancer stage (Baalen et al, 2020). However, our study found that the cancer stage was significantly correlated with the level of hope.…”
Section: Discussionmentioning
confidence: 99%